International investment position of European countries – chosen aspects - Maciejczyk-Bujnowicz, Iwona (Acta Universitatis Lodziensis. Folia Oeconomica, 2017)
The paper aims at assessing the changes in flows of selected forms of capital under deepening financial integration in the European Union. EU Member States are divided into two groups: members of the euro area and those outside of it. The analysis coincides with the establishing of the EU monetary union and covers the turn and early 21st century. We have reviewed major theoretical concepts providing grounds for further considerations. Together with the progressing financial integration of the EU Member States there is an increase in the overall value of financial flows measured with net IIP. Research method applied in this particular study includes the overview of theoretical concepts, literature review and a comparative analysis based on statistical data. Analyses of selected data revealed significant differences between developed and developing countries when it comes to various forms of net capital and its relation to the GDP based on the International Investment Position. The analysis of the degree of financial and trade integration of the Eurozone countries compared to the Member States outside of the euro area demonstrated that the two groups are at two opposite extremes.